In vitro safety assessment of food ingredients in canine renal proximal tubule cells. Issue 2 (March 2015) - Koči, J.; Jeffery, B.; Riviere, J.E.; Monteiro-Riviere, N.A.
Highlights In vivo kidney injury markers (e.g. KIM-1) are not applicable to an in vitro model Volatile ingredients (CINA, CBO, LGO) studied are more toxic than the nephrotoxicant 4-AP Feasibility of extrapolating data from canine cells for human toxicity studies Lemongrass oil (LGO) induces high levels of oxidative stress represented by GSTA3 Gene relationship and TEM analyses predict the LGO-induced cellular response